Pedagogical Conditions of Practical Training of Future Technician-Technologist in the Specialty «Production of Bread, Confectionery, Pasta and Food Concentrates» - Tkach, Liliia (Pedagogical Discourse, 2019)
The article provides a methodological substantiation of the practical training pedagogical conditions of the future technicians in the specialty «Production of bread, confectionery, pasta and food concentrates» in the food industry colleges, contribute to the formation of practical skills and professionally important qualities and constitute the practical basis of their professional competence. Pedagogical conditions are defined as a set of favorable system pedagogical circumstances in colleges, which are consciously created by teachers for targeted practical training of the future technicians-technologists. It is noted that these conditions should contain the following aspects of their practical training. Methodological: the main leading ideas and practical training principles, on the basis of which their practical preparation takes place. This is a competence for the unison, contextual and subject-activity approaches. Theoretical: goal, aims, principles, content and the result of their practical preparation for the future professional activity, in particular. Methodical: the main methods, technologies, tools and the author’s method of practical training of technicians-technologists in the specialty «Production of bread, confectionery, pasta and food concentrates.» Practical: the availability of modern material and technical base of practical training that meets the food production requirements and the specifics of the future professional activity of graduates. Reasonable pedagogical conditions create optimal conditions for the training of the future technicians-technologists in the specialty «Production of bread, confectionery, pasta and food concentrates.» These conditions are: 1) pedagogical modeling of their practical training in colleges; 2) presence of a modern integrated phased author’s methodology for their practical training; 3) providing self-management of students in the practical training processf; 4) objective criteria usage for assessing the levels of their practical readiness.